Effect of cassava peel levels in fermented total mixed ration (FTMR) used Napier Pakchong as roughage on feed intake, ruminal fermentation and nutrient digestibility in beef cattle - Songsak Chumpawadee (Warasan Witthayasat Lae Theknoloyi Mahawitthayalai Mahasarakham, 2019)
The objective of this study was to determine the effect of cassava peel levels in fermented total mixed ration used Napier Pakchong as roughage on feed intake, ruminal fermentation and nutrient digestibility in beef cattle. Four Brahman-Thai native crossbred cattle with an average initial body weight of 180.25 ± 16.25 kg were randomly assigned in a 4x4 Latin Square Design. During each of four 21 day periods, the animals were fed four dietary treatments. The treatments were fermented total mixed ration with different amounts of cassava peel 0, 15, 30, and45 %, respectively. The results showed that feed intake was significant different among treatment (P<0.05). The digestibility, ruminal pH, ammonia–nitrogen and total volatile fatty acid were not significantly different (P>0.05). Therefore, suitable levels of cassava peels in fermented total mixed ration ranged from 15-30 %, and did not affect feed intake, nutrient digestibility and ruminal fermentation.